Incidence and risk factors of hepatic fibrosis in psoriatic patients receiving methotrexate with concomitant acitretin therapy and methotrexate monotherapy - Ploysyne Rattanakaemakorn (2022)
Background: The use of methotrexate-acitretin (MTX-ACI) combination therapy in treating psoriasis has been limited due to concerns related to hepatic fibrosis. However, in vitro evidence revealed a protective effect of acitretin in methotrexate (MTX)-induced liver fibrosis. Objective: This study aimed to compare the real-life incidence of hepatic fibrosis in patients with psoriasis receiving MTX-ACI and MTX monotherapy and to investigate factors associated with hepatic fibrosis in MTX-exposed patients. Methods: A retrospective cohort study was conducted based on a real-life registry containing data on patients with psoriasis who were administered MTX-ACI or MTX between 2008 and 2019 and underwent transient elastography according to cumulative MTX dose of 1.0–1.5 g and/or 3.5–4.0 g. Time-to-event analysis was performed to determine the cumulative inci-dence, incidence rate, and factors potentially affecting the occurrence of hepatic fibrosis. Results: Of the 160 patients, 32 (20%) were treated with MTX-ACI, and 128 (80%) with MTX alone. Four patients (12.5%) in MTX-ACI group and 21 (16.4%) in MTX group developed hepatic fibrosis (p = 0.59). There was no statistically significant difference in cumulative incidence (16% in MTX-ACI vs 17% in MTX, p = 0.89) and incidence rate (37 cases per 1000 person-year in MTX-ACI vs 23 cases per 1000 person-year in MTX; hazard ratio [HR] = 1.07; p = 0.90) of hepatic fibrosis between the two groups. Diabetes and obesity were identified as significant factors associated with hepatic fibrosis (adjusted HR = 2.40, 95% confidence interval [CI]: 1.05–5.51; p = 0.04 and adjusted HR = 3.28, 95% CI: 1.18–9.16; p = 0.02, respectively) regardless of the cumulative MTX dose. Conclusion: The incidence of hepatic fibrosis in a real-life clinical situation, determined by transient elastography in patients with psoriasis receiving MTX-ACI, was not increased com-pared to those receiving MTX monotherapy. Type 2 diabetes mellitus and obesity were identified as risk factors of hepatic fibrosis; hence, patients with these factors receiving long-term MTX therapy should be regularly monitored for this particular event.